PENGARUH MERGER TERHADAP RENTABILITAS PADA BANK DANAMON (STUDI KASUS DI BURSA EFEK SURABAYA) - Hayatul Maemunah (Universitas PGRI Madiun, 2017)
ABSTRACTAs one of the financial instruments, the Bank plays a very important role, because the supervision of banking activities is increasingly being improved. However, with the current monetary crisis in Indonesia and the continuing turmoil of the political situation, it has brought the Indonesian banking industry into a really difficult situation. Considering the condition of this National Bank, the government decided to liquidate private banks with low performance. In the framework of national banking restructuring, the government also proposed to merge some national private banks and state-owned banks. This merger step has a strategic goal, namely to form a larger merged bank, strengthening the capital structure, has a comparative advantage as well as a stronger competitiveness in this globalization. The purpose of this study is to know the effect of merger on the level of profitability at Bank Danamon. The type of research used in this study is descriptive research while for data collection authors use secondary data. The population of this study include 9 Bank Take Over and samples taken as many as two banks, using purposive sampling technique. The analytical model used is, the analysis using the financial ratios of Gross Profit Margin, Net Profit Margin, Return On Investment, and return On eqiuty and Test T. The results show that: (1) Bank Danamon Tbk is a merged bank between Bank Danamon With Bank Take Over (Tiara Asia Bank, Risjad Salim Bank, Duta Bank, Tamara Bank, Bank Nusa Nasional, Rama Bank, Bank Jaya and Bank Pos Nusantara). (2) The implementation of the merger has a positive impact on the level of profitability at Bank Danamon. (3) There is a significant difference between profitability before and after merger, it can be seen from result of t test which show that tcount (4,039) is bigger than ttable (3,182).Keywords: Merger, Profitability